Discrete dislocation plasticity HELPs understand hydrogen effects in bcc materials. (February 2019) - Yu, Haiyang; Cocks, Alan; Tarleton, Edmund
Abstract: In an attempt to bridge the gap between atomistic and continuum plasticity simulations of hydrogen in iron, we present three dimensional discrete dislocation plasticity simulations incorporating the hydrogen elastic stress and a hydrogen dependent dislocation mobility law. The hydrogen induced stress is incorporated following the formulation derived by Gu and El-Awady (2018) which here we extend to a finite boundary value problem, a microcantilever beam, via the superposition principle. The hydrogen dependent mobility law is based on first principle calculations by Katzarov et al. (2017) and was found to promote dislocation generation and enhance slip planarity at a bulk hydrogen concentration of 0.1 appm; which is typical for bcc materials. The hydrogen elastic stress produced the same behaviour, but only when the bulk concentration was extremely high. In a microcantilever, hydrogen was found to promote dislocation activity which lowered the flow stress and generated more pronounced slip steps on the free surfaces. These observations are consistent with the hydrogen enhanced localized plasticity (HELP) mechanism, and it is concluded that both the hydrogen elastic stress and hydrogen increased dislocation mobility are viable explanations for HELP. However it is the latter that dominates at the low concentrations typically found in bcc metals.